New Dephenylated Analogues of (–)-Goniofufurone: Optimization of Synthesis from l-Xylose - Stanisavljević, Sladjana; Popsavin, Mirjana; Kojić, Vesna; Benedeković, Goran; Popsavin, Velimir; Zelenović, Bojana Srećo (Synlett, 2024)
Natural products containing highly oxygenated furanofuranone fragments are known for their potent biological activity, but also for their challenging total synthesis. In this study, the synthesis of five novel dephenylated (–)-goniofufurone analogues was completed and their cytotoxic activity against eight malignant and one normal human cell line was evaluated. Compared with previous syntheses of similar analogues, the synthesis was carried out starting from l-xylose, resulting in improved yields and a reduced number of synthetic steps for three divergent intermediates.
Keywords: goniofufurone; lactones; bicycles; cytotoxicity; Meldrum’s acid